Comparison of the Analagesic Efficacy of Transdermally Applied Buprenorphine and Ketoprofen for Postoperative Abdominal Pain in Dogs - Singh, Tanya; Jain, Reshma; Dangi, Rakesh; Shukla, BP; Shrivastava, Nidhi (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Transdermal drug delivery (TDD) is defined as the non-invasive delivery of medications through the skin surface. The present study was planned to evaluate the efficacy of transdermal drug delivery system to alleviate the post-operative pain after abdominal surgery. Twelve clinical cases of dogs presented to the Department of Veterinary Surgery and Radiology, VCC, College of Veterinary Science and A.H., Mhow were selected for the study and divided into two groups. In group I (n=6) ketoprofen transdermal patch and in group II (n=6) buprenorphine transdermal patch was applied to the skin. The Glasgow Composite Measure Pain Scale was used to assess the pain pre-operatively (1 hour before surgery), complete post recovery, 24, 48 and 72 h post operatively. The mean total pain score was maximum in ketoprofen group than the buprenorphine group. Serum glucose and serum cortisol values increased significantly (P
Keywords: Abdominal surgery; Buprenorphine; Composite Measure Pain Scale (GCMPS),; Glasgow; Ketoprofen; Transdermal patch